The Infrastructure We Ride On Decision Making in Transportation Investment - Berechman, Joseph (Springer International Publishing, 2018)
This book explores the various economic and institutional factors that explain why huge investments are made in unworthy transportation mega-projects in the US and other countries. It is based on research, the general literature, economic analyses, and results from a specifically collected database showing that a significant proportion of implemented mega-projects have been found to be inferior ex-ante or incapable of delivering the returns they promised ex-post. Transportation infrastructure and other public investments of a similar scope ("mega-projects") reflect public sector priorities and objectives, non-pecuniary as well as financial constraints, and a range of decision-making processes. This book describes how decisions made in the public sector with respect to transportation infrastructure investments are affected by the large populations and territories they serve, the estimation of the substantial opportunity costs they entail, the formal procedures instituted for quantitatively appraising projected outcomes and monetary returns, and the political environment in which these decisions are made.